2008
DOI: 10.1038/nm.1887
|View full text |Cite
|
Sign up to set email alerts
|

5′-triphosphate-siRNA: turning gene silencing and Rig-I activation against melanoma

Abstract: Genetic and epigenetic plasticity allows tumors to evade single-targeted treatments. Here we direct Bcl2-specific short interfering RNA (siRNA) with 5'-triphosphate ends (3p-siRNA) against melanoma. Recognition of 5'-triphosphate by the cytosolic antiviral helicase retinoic acid-induced protein I (Rig-I, encoded by Ddx58) activated innate immune cells such as dendritic cells and directly induced expression of interferons (IFNs) and apoptosis in tumor cells. These Rig-I-mediated activities synergized with siRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
386
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 353 publications
(408 citation statements)
references
References 31 publications
13
386
1
Order By: Relevance
“…26 Given the rising incidence of melanoma and the paucity of effective treatments, there is much hope for targeted therapies and promising agents, including those that act on apoptosisregulating molecules. 11,27 Herein, we showed a novel role for FKBP51 as a marker of melanocyte malignancy and involvement in the protection of melanoma against Rx-induced apoptosis. FKBP51 is a large immunophilin that exerts important biological functions in the cell, among which is the regulation of the steroid hormone response as a component of the steroid hormone receptor complex 28 and the control of NF-kB activation as a cofactor of the IKKa subunit in the IKK complex.…”
Section: Discussionmentioning
confidence: 94%
“…26 Given the rising incidence of melanoma and the paucity of effective treatments, there is much hope for targeted therapies and promising agents, including those that act on apoptosisregulating molecules. 11,27 Herein, we showed a novel role for FKBP51 as a marker of melanocyte malignancy and involvement in the protection of melanoma against Rx-induced apoptosis. FKBP51 is a large immunophilin that exerts important biological functions in the cell, among which is the regulation of the steroid hormone response as a component of the steroid hormone receptor complex 28 and the control of NF-kB activation as a cofactor of the IKKa subunit in the IKK complex.…”
Section: Discussionmentioning
confidence: 94%
“…A recently published study has shown that tri-phosphate-containing siRNAs, which are potent triggers of type I interferon induction, resulted in potent inhibition of metastatic melanoma tumor progression in a murine model. 12 For treatment of other conditions though, the dual effect may not be beneficial, and only the sequence specificity of the siRNA would be useful. It will require judicious testing of backbone modifications and delivery mechanisms in vivo to ensure siRNA applications are only targeting the desired transcripts so specific gene downregulation is the sole cause of observed phenotypes. '…”
Section: News and Commentarymentioning
confidence: 99%
“…[5][6][7] Ligands targeting the RLR, RIG-I, and MDA-5 are also currently under development for cancer immunotherapy. 4,8,9 To transmit intracellular signaling, RLR and TLR employ different adaptor molecules; RLR utilize MAVS, 10 whereas TLR are coupled to MyD88 with the exception of TLR3, which exclusively signals via the adaptor TRIF. 11 Due to the different pathways triggered, cross-talk of receptor families can lead to enhanced immune responses.…”
Section: Introductionmentioning
confidence: 99%